(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article provides detailed information on the laws of the development of the library-information activity system, methods of mutual cooperation between the library and information institutions, and the social efficiency of using the information collected in the library-information activity system.